ANALISIS RASIO ARUS KAS DALAM MENILAI KINERJA KEUANGAN PADA PT. PLN (PERSERO) WILAYAH SULUTTENGGO - Warongan, Megi Sila Jona; Ilat, Ventje; Gerungai, Natalia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Cash is one of the most liquid account compared to the other accounts within the company’s balance sheet. The statements of cash flow contains information of actual cash position occurring in the company’s operational activities. By using cash flow ratios, development of the company’s financial performance from year to year can be analyzed. This study aims to determine and assess financial performance based on cash flow ratios in PT. PLN (Persero) Suluttenggo Region, by using a descriptive method with a quantitative approach. The results showed that the state of PT. PLN (Persero) Suluttenggo Region’s financial performance is less good. This is because four of the five cash flow ratios assessed experienced a decrease from the ratio in 2014, and only the ratio of cash flow to interest in 2016 increased from the previous years. Increasing the company’s cash is very important for PT. PLN (Persero) Suluttenggo Region, especially on operational activities which is the main activity of the company’s cash so that in the future, the company’s financial performance will get better.Keywords: cash, cash flow ratio, cash flow statement, financial performance